Theory of Change: The Client’s Perspective on the Nature of Change in Psychotherapy - Goryczko, Magdalena (Curtin University, 2015)
The aim of this study was to discover specific factors that facilitate therapeutic change as perceived by clients. This study utilised Interpretative Phenomenological Analysis (IPA) and the data were collected from therapists and non-therapists who had completed a medium to long-term therapy. Findings suggest that change was a deeply relational process experienced, not as distinct stage-like phases, but rather as a gradual development of new structures of alignment in the cognitive, affective, and bodily domains.